The Other Women's Lib Gender and Body in Japanese Women's Fiction - Bullock, Julia C. (University of Hawaii Press, 2010)
Their fictional heroines are unapologetically bad wives and even worse mothers; they are often wanton, excessive, or selfish and brazenly cynical with regard to traditional love, marriage, and motherhood.The Other Women’s Lib affords a cogent and incisive analysis of these texts as feminist philosophy in fictional form, arguing persuasively for the inclusion of such literary feminist discourse in the broader history of Japanese feminist theoretical development. It will be accessible to undergraduate audiences and deeply stimulating to scholars and others interested in gender and culture in postwar Japan, Japanese women writers, or Japanese feminism